The Influence of Product Quality and Price on Consumer Purchase Interest at Nay Kids Store - Saputra, Adam (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
This study examines the influence of product quality and price on consumer purchase interest at Nay Kids Store in Banjarmasin. The population in this study consists of 206 consumers, and using the Slovin formula, a sample of 67 consumers who made bulk purchases of clothing was obtained. Quantitative analysis was conducted, including validity and reliability tests on the research instruments, as well as hypothesis testing through classical assumption tests, F-test, t-test, partial correlation, and multiple regression analysis. The results indicate that both product quality and price simultaneously affect purchase intention. Specifically, product quality  and price also show significant partial effects on purchase intention. Additionally, product quality has the strongest influence, with the highest partial correlation coefficient. These findings highlight the importance of product quality as the most dominant factor in influencing consumer purchase intention, providing valuable insights for retailers who aim to enhance customer satisfaction and sales performance.